Monet's minutes Impressionism and the industrialization of time - Dombrowski, André (Yale University Press, 2023)
"Monet's Minutes is a revelatory account charting the relationship between the works of Claude Monet (1840-1926)--founder of French Impressionism and one of the world's best-known painters--and the modern experience of time. Andř Dombrowski illuminates Monet's celebration of instantaneity in the context of the late nineteenth-century time technologies that underwrote it. Monet's version of Impressionism demonstrated an acute awareness of the particularly modern pressures of time, but until now scholars have not examined the histories and technologies of time and timekeeping that informed Impressionism's major stylistic shifts. Arguing that the fascination with instantaneity rejected the dulling cultures of newly routinized and standardized time, Monet's Minutes traces the evolution of Monet's art to what were then seismic shifts in the shape of time itself. In each chapter, Dombrowski focuses on the connections between a set of Monet's works and a specific technology or experience of time, while providing the voices of period critics responding to Impressionism"-- Publisher's description